2014
DOI: 10.4238/2014.september.12.18
|View full text |Cite
|
Sign up to set email alerts
|

Association of MLL3 expression with prognosis in gastric cancer

Abstract: ABSTRACT. Low expression of myeloid/lymphoid or mixed-lineage leukemia 3 (MLL3) is reportedly associated with gastric cancer and tumor progression. The purpose of this study was to examine the expression of MLL3 in tissue samples of patients with gastric cancer and to analyze the relationship between MLL3 protein expression and clinical records. Using immunohistochemical staining and KaplanMeier analysis for MLL3 in gastric cancer patients, we found that low expression of MLL3 had a significant relationship wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 9 publications
(8 reference statements)
2
11
0
1
Order By: Relevance
“…Moreover, the cellular localization of KMT2C, both nuclear and cytoplasmic, was confirmed by immunofluorescence analysis. The nuclear localization of KMT2C agrees with its function as co-activator of transcriptional factors while the cytoplasmic localization, that was already described for KMT2C [ 20 ], showed that there was an altered intracellular localization of KMT2C (nuclear-cytoplamic trafficking). Recent evidence shows that specific variations of KMT2C can lead to different effects, including the inactivation of the protein or a change in the enzymatic activity [ 21 ].…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, the cellular localization of KMT2C, both nuclear and cytoplasmic, was confirmed by immunofluorescence analysis. The nuclear localization of KMT2C agrees with its function as co-activator of transcriptional factors while the cytoplasmic localization, that was already described for KMT2C [ 20 ], showed that there was an altered intracellular localization of KMT2C (nuclear-cytoplamic trafficking). Recent evidence shows that specific variations of KMT2C can lead to different effects, including the inactivation of the protein or a change in the enzymatic activity [ 21 ].…”
Section: Discussionsupporting
confidence: 77%
“…These results showed that Mll1, Mll3, Ash2l, Wdr5, Rbbp5, Jmjd3, and Utx, are all expressed in insulin positive cells ( Fig 6C ). Interestingly, although Dpy30 staining was predominantly nuclear, all the other proteins showed staining in both the cytoplasm and the nucleus as has been previously determined [ 45 48 ]. Together, these data confirm that TrxG proteins are present within β-cells and, given that these complexes can contain both H3K4 histone methyltransferase activity and H3K27me3 demethylase activity, are likely at least partly responsible for the IFNγ, Il-1β, and TNFα mediated conversion of inactive, repressed and bivalent cis-regulatory loci into active loci.…”
Section: Resultssupporting
confidence: 75%
“…As we have verified that MLL3 expression level was upregulated in the DCM hearts compared with donor hearts, we hypothesized that the expression levels of Smad3, GATA4 and EGR1 would increase in the hearts of DCM melanoma and pancreatic cancer (37)(38)(39)(40). However, no research has investigated the function of MLL3 on heart diseases currently.…”
Section: Discussionmentioning
confidence: 98%